A COMPARATIVE ANALYSIS OF LINGUISTIC STEREOTYPES AND SOCIAL NORMS IN UZBEK AND ENGLISH PROVERBS BASED ON CONCEPT OF GENDER - Yakhyoeva Gulkhumor Shukhrat qizi; Nurmatova Mutabar Shuhrat qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article examines the intricate relationship between gender, language, and culture, focusing on how linguistic stereotypes perpetuate societal norms. By analyzing communication patterns associated with men and women, the study reveals the significant influence of cultural and historical contexts on speech. Using examples from English and Uzbek proverbs, the article highlights how gender roles are encoded in language, reinforcing traditional expectations and behaviors. It argues that understanding these linguistic constructs is essential for fostering awareness and promoting gender equality in communication. Ultimately, the research underscores the importance of evolving language practices to challenge entrenched stereotypes and facilitate a more equitable discourse.